The Effectiveness of Drill Smash Practice Methods and Multishuttle Play Methods on Badminton Smash Accuracy in High School Extracurricular Students - M. Jumadil Awal; Ali Muhaimin; Johan Wahyudi (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
The accuracy of the smash is an important indicator of badminton performance because it determines the effectiveness of attacks, the ability to pressure the opponent, and the chances of earning points. This study was compiled based on the premise that the improvement of smash accuracy depends not only on the ability to hit the shuttlecock strongly, but also on training methods that are able to form technique consistency, movement response, and the ability to direct the punch to the target area. The purpose of this study was to analyze the change in the accuracy of students' smash after being given the training treatment and to compare the final achievement between the drill smash training group and the multishuttle play method group. The study used a quantitative approach with a design of two pretest-posttest groups. The research subjects amounted to 21 extracurricular badminton students, consisting of 10 students in group 1 and 11 students in group 2. Data was collected through smash precision tests before and after treatment. The results of descriptive statistics show that the total pretest score of 300 increased to 336 in the posttest. The average score also increased from 14.2857 to 16.0000, with a decrease in standard deviation from 1.52128 to 1.30384. These results show a tendency to improve overall smash accuracy after the training treatment. The Shapiro-Wilk normality test showed that the pretest data in both groups were normally distributed, while the posttest data were not normally distributed. Posttest comparison showed that group 2 obtained an average higher than group 1, which was 16.2727 compared to 15.7000. However, the effect size showed Cohen's d of -0.439 with a 95% confidence interval from -1.301 to 0.434, so the differences between groups could not be statistically strong. Thus, the hypothesis that exercises improve smash accuracy is supported descriptively, but the superiority of either method needs to be further tested with a more complete inferential analysis.   Keywords: Precision Smash; Drill Smash; Multishuttle; Badminton; Pretest-Posttest.